2007
DOI: 10.1038/sj.ki.5002623
|View full text |Cite
|
Sign up to set email alerts
|

Antiproteinuric effect of the calcium channel blocker cilnidipine added to renin-angiotensin inhibition in hypertensive patients with chronic renal disease

Abstract: Cilnidipine, a dual L-/N-type calcium channel blocker, dilates both efferent and afferent arterioles and is renoprotective. Our multi-center, open-labeled, and randomized trial compared the antiproteinuric effect of cilnidipine with that of amlodipine in hypertensive patients with kidney disease. A group of 339 patients, already receiving renin-angiotensin system inhibitor treatment, were randomly assigned to cilnidipine or amlodipine. The primary endpoint was a decrease in the urinary protein to creatinine ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
112
6
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 39 publications
(53 reference statements)
10
112
6
1
Order By: Relevance
“…5,8 The Cilnidipine vs. Amlodipine Randomized Trial for Evaluation in Renal Disease study showed that cilnidipine was more beneficial than amlodipine in hypertensive patients. 7 Besides RAS inhibition, strict control of BP is considered important for preventing the progression of kidney disease. 15,17,18 Both cilnidipine and amlodipine effectively reduced BP level in hypertensive patients after 6 months of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,8 The Cilnidipine vs. Amlodipine Randomized Trial for Evaluation in Renal Disease study showed that cilnidipine was more beneficial than amlodipine in hypertensive patients. 7 Besides RAS inhibition, strict control of BP is considered important for preventing the progression of kidney disease. 15,17,18 Both cilnidipine and amlodipine effectively reduced BP level in hypertensive patients after 6 months of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 Furthermore, cilnidipine was shown to be more beneficial than amlodipine in combined treatment for hypertensive patients with kidney disease and significant proteinuria who were receiving treatment with a renin-angiotensin system (RAS) inhibitor. 7 The beneficial effect of cilnidipine might be attributable to the inhibition of renal sympathetic nerve activity 8 and reduction of glomerular hypertension (because of the vasodilation of efferent arterioles), which are consequences of the N-type calcium channel blockade. However, the precise mechanism underlying the renoprotective effect of cilnidipine remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…CCBs, however, can be divided into several subtypes. Cilnidipine, which is reported to protect against cardiovascular [27][28][29] and kidney disease, [30][31][32] works in a variety of ways, including blocking the N-type calcium channel and the L-type calcium channel. Recently, cilnidipine has also been reported to suppress renin activity and inhibit the renal renin-angiotensin system.…”
Section: Cilnidipine and Osteoporosis Hideo Shimizu Et Almentioning
confidence: 99%
“…14,15 However, it has recently been reported that both a dual L-/N-type CCB cilnidipine and an L-/T-type CCB efonidipine exhibit a greater antiproteinuric effect than does amlodipine. 16,17 Benidipine, another dual L-/T-type CCB, dilates both efferent and afferent arterioles and reduces glomerular pressure. 18 Therefore, benidipine also may exert renoprotective effects.…”
Section: Introductionmentioning
confidence: 99%